Lost Marvels. No. 3, Savage tales of the 1980s. (Lost Marvels, 2025)
For 13 months in the mid-1980s, Marvel assembled some of its strongest artists and writers to tell gritty, harrowing, and darkly humorous adventure stories ranging from gangster noir to historical battlefields to the deadly old West to post-apocalyptic futures. Unseen for nearly 40 years, here is some of the most shocking work of artists John Severin, John Buscema, Sam Glanzman, Val Mayerik, Ron Wagner, Grey Morrow, Wayne Vansant, Herb Trimpe, Michael Golden, Joe Jusko, Mary Wilshire, Arthur Suydam, Will Jungkuntz, Vincent Waller, Ralph Reese, Bill Wray, and Ken Steacy, and writers Chuck Dixon, Robert Kanigher, Denny O'Neil, Doug Murray, and Archie Goodwin. Stories include Severin and Dixon's "By Rail to Vladivostock," Murray and Golden's "The Nam, 1967," Glanzman's "Of War and Peace: The Trinity," Jungkuntz' Blood & Gutz series, and Trimpe's Skywarriors series. With a remembrance by Savage Tales editor Larry Hama.